Phase Segregation Enhanced Ion Movement in Efficient Inorganic CsPbIBr2 Solar Cells. Issue 20 (12th July 2017) - Li, Wei; Rothmann, Mathias Uller; Liu, Amelia; Wang, Ziyu; Zhang, Yupeng; Pascoe, Alexander R.; Lu, Jianfeng; Jiang, Liangcong; Chen, Yu; Huang, Fuzhi; Peng, Yong; Bao, Qiaoliang; et al.
Abstract: Organic–inorganic hybrid perovskite solar cells with mixed cations and mixed halides have achieved impressive power conversion efficiency of up to 22.1%. Phase segregation due to the mixed compositions has attracted wide concerns, and their nature and origin are still unclear. Some very useful analytical techniques are controversial in microstructural and chemical analyses due to electron beam‐induced damage to the "soft" hybrid perovskite materials. In this study photoluminescence, cathodoluminescence, and transmission electron microscopy are used to study charge carrier recombination and retrieve crystallographic and compositional information for all‐inorganic CsPbIBr2 films on the nanoscale. It is found that under light and electron beam illumination, "iodide‐rich" CsPbI(1+ x ) Br(2− x ) phases form at grain boundaries as well as segregate as clusters inside the film. Phase segregation generates a high density of mobile ions moving along grain boundaries as ion migration "highways." Finally, these mobile ions can pile up at the perovskite/TiO2 interface resulting in formation of larger injection barriers, hampering electron extraction and leading to strong current density–voltage hysteresis in the polycrystalline perovskite solar cells. This explains why the planar CsPbIBr2 solar cells exhibit significant hysteresis in efficiency measurements, showing an efficiency of up to 8.02% in the reverse scan and a reduced efficiency of 4.02% in the forward scan, and giving a stabilized efficiency of 6.07%. Abstract : Iodide‐rich phase segregation near grain boundaries and the formation of iodide‐rich "clusters" inside the film are observed in the CsPbIBr2 perovskite thin films. The mobile ions generated by the phase segregation, moving alone grainboundaries and piling up at CsPbIBr2 /TiO2 interface, can become charge injection barriers and exacerbate the current density–voltage hysteresis in inorganic CsPbIBr2 solar cells.